Educação Ambiental e as Novas Tecnologias de Informação e Comunicação / Environmental education and the new comunication and information technologies - Marlene Teresinha Muno Colesanti; Gelze Serrat Souza Campos Rodrigues (Sociedade & Natureza)
In the last twenty years, the development of modern information and communication technologies, aswell as the enlarging of their use have created enormous expectations and possibilities on schoolteaching. Related to the Environmental Education, the use of modern information and communicationtechnologies represents an advance, since the integration of information technology and multimediaallows the sensitive and knowledge of different environments and their specific problems, by the viewof students, as far as they can be.Through of the conception of Environmental Education linked to the complexity pedagogy, this articlelooked for argue the potentiality of work with principles of Environmental Education on support digital,using images, texts and sounds, implemented by hypermedia, no sequential technology, which informationare accessed in associative way.Keywords: Environmental Education. Hypermedia. Modern information and comunication.